Computer-Assisted Volumetric Analysis and Quantitatively Anophthalmic Orbit Reconstruction With Dorsalis Pedis Flap and Bone Graft. Issue 2 (March 2018) - Cheng, Li-Ying; Bian, Wei-Wei; Sun, Xiao-Ming; Yu, Zhe-Yuan; Zhang, Ying; Zhang, Lu; Zhang, Yu-Guang; Jin, Rong
Abstract : Abstract: Current approaches to orbit reconstruction are based on the assumption of facial symmetry and surgeons' experiences, and the reconstructed orbits are not precise. Through computer-assisted volumetric quantitative analysis, the volume of the bony orbit, and the volume of the soft tissues in both the anophthalmic orbit and the contralateral orbit are calculated in 39 anophthalmic patients. The rib graft is used for orbit reconstruction; the dosalis pedis flap and lipo-injection were used for soft tissue reconstruction and skin socket reconstruction. The size and the shape of the rib graft and soft tissues were designed according to the volumetric analysis. The size and the shape of the skin socket were designed according to measurement during surgery. Asymmetry eye sockets with adequate size were created in the 37 patients. Two patients presented with a poor asymmetry with the contralateral orbit, and got gradual extrusion of the eye prosthesis 4 months after operation, which was because of necrosis of the flaps. The flaps were remedied by frontal island flap and skin grafting. Further surgeries, such as lipoinjection, lid surgery, and canthoplasty, were applied to improve the surgical results. The eye prostheses fitted well in all of the reconstructed sockets using this technique. Our studies suggest that the computer-assisted volumetric analysis technique combined with quantitative bone graft and dorsalis pedis flap transfer, ± lipoinjection proved to be an accurate method and a quality assurance for optimization of bony orbit, soft tissue and skin socket reconstruction, and promised a successful postoperative outcome for patients' functional and esthetic appearance.